The Development of Russian Multinational Enterprises From the 1990s to the Present - Anna Zubkovskaya; Snejina Michailova (Organizations and Markets in Emerging Economies, 2014)
While the internationalization of Russian multinational enterprises (MNEs) has increased significantly since the early 2000s, this phenomenon has attracted limited attention among scholars. In the present paper we examine the key characteristics of Russian MNEs and use the literature on emerging market multinationals and Dunning’s OLI paradigm to trace Russian MNEs’ development from the 1990s to the present. We analyze this development, particularly in regard to ownership structure, location choices, entry modes, and motives to internationalize. We analyze how Russian MNEs have evolved into powerful entities and contributed to Russia’s modernization and integration into the global economy.